ANALISIS PERGESERAN KONSENTRASI PENDUDUK PERKOTAAN DAN PROYEKSI KEBUTUHAN STANDAR PELAYANAN MINIMAL DI KOTA SINTANG TAHUN 2020 - SYARIF, RIANDY (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT This study aims to determine the direction of the concentration of population shifts to 2020 and to determine the needs of Urban Public Service Facilities in District Sintang year 2020. By using the method of projection Geomethric Growth rate refers to the base year 2000 and 2010 results showed that the concentration of the population leads to a shift away from the city center. While using Decree of the Minister of Human Settlements and Infrastructure area No.534/KPTS/M/2001 on Guidelines for Determination of Minimum Service Standards Field of Spatial Planning, Housing and Human Settlements and Public Works and the Indonesian National Standard No.03-1733-2004 on Procedures Housing in Urban Environmental Planning, then known public service facilities required by 2020 increasing. Keywords: Shifting Population Projections Minimum Service Standards